Comparison of GCM‐ and RCM‐simulated precipitation following stochastic postprocessing. Issue 19 (6th October 2014) - Eden, Jonathan M.; Widmann, Martin; Maraun, Douglas; Vrac, Mathieu
Abstract: In order to assess to what extent regional climate models (RCMs) yield better representations of climatic states than general circulation models (GCMs), the output of each is usually directly compared with observations. RCM output is often bias corrected, and in some cases correction methods can also be applied to GCMs. This leads to the question of whether bias‐corrected RCMs perform better than bias‐corrected GCMs. Here the first results from such a comparison are presented, followed by discussion of the value added by RCMs in this setup. Stochastic postprocessing, based on Model Output Statistics (MOS), is used to estimate daily precipitation at 465 stations across the United Kingdom between 1961 and 2000 using simulated precipitation from two RCMs (RACMO2 and CCLM) and, for the first time, a GCM (ECHAM5) as predictors. The large‐scale weather states in each simulation are forced toward observations. The MOS method uses logistic regression to model precipitation occurrence and a Gamma distribution for the wet day distribution, and is cross validated based on Brier and quantile skill scores. A major outcome of the study is that the corrected GCM‐simulated precipitation yields consistently higher validation scores than the corrected RCM‐simulated precipitation. This seems to suggest that, in a setup with postprocessing, there is no clear added value by RCMs with respect to downscaling individual weather states. However, due to the different ways of controlling the atmospheric circulation in the RCM and the GCM simulations, such a strong conclusion cannot be drawn. Yet the study demonstrates how challenging it is to demonstrate the value added by RCMs in this setup. Key Points: Comparison between bias‐corrected RCMs and bias‐corrected GCMs The first application of stochastic MOS for GCM precipitation It is challenging to demonstrate the value added by RCMs in this setup